"Evil Cats" and "Jelly Floods": Young Children's Collective Constructions of Digital Art Making in the Early Years Classroom. Issue 1 (2nd January 2016) - Sakr, Mona; Connelly, Vince; Wild, Mary
ABSTRACT: Digital technologies have the potential to offer new opportunities for children's expressive arts practices. Although adult expectations surround and shape children's visual art making on paper in the early years classroom, such expectations are not so established in relation to digital art making. So how do children make sense of digital art making when it is newly introduced into the classroom and adult input is minimal? Drawing on a social semiotic ethnographic perspective, this study explores this question by examining instances of 4- to 5-year-olds' spoken dialogue around the computer during a week in which digital art making was first introduced into the classroom. Analysis focused on interactions where children proposed, reinforced, or challenged conceptions of digital art making. These interactions demonstrated that children's digital art making was negotiated and constructed through particular processes. Three such processes are presented here: the use of collective motifs and metaphors, attributing "expert" status, and polarizing conflicts. Understanding these processes offers a starting point for thinking about how a new activity like digital art making can be integrated into the early years classroom and supported by practitioners.